Preparation of Trifluoromethylated (Arylaminomethylene)malononitriles Suitable for Synthesis of 4-Amino-2-(trifluoromethyl) quinoline Derivatives by Intramolecular Friedel–Crafts Reaction - Rahmani, Fariba; Darehkordi, Ali (Synthesis, 2018)
An approach for the synthesis of 4-amino-2-(trifluoromethyl)quinolines via the intramolecular Friedel–Crafts reaction of 2-(1-(arylamino)-2,2,2-trifluoroethylidene)malononitrile derivatives is reported. This simple protocol provides a wide variety of 4-amino-2-(trifluoromethyl)quinolines in good to excellent yields, without any purification. Furthermore, the 2-(1-(arylamino)-2,2,2-trifluoroethylidene) malononitrile derivatives used in this project have been synthesized by the reaction of N-aryl-2,2,2-trifluoroacetimidoyl chlorides and malononitrile at ambient temperature and under microwave irradiation in excellent yields, for the first time.
Keywords: 4-amino-2-(trifluoromethyl)quinolones; intramolecular Friedel–Crafts reaction; trifluoromethylated (arylaminomethylene)malononitriles; trifluoroacetimidoyl chlorides; trifluoromethylated compounds